Design, synthesis, in silico studies, and apoptotic antiproliferative activity of novel thiazole-2-acetamide derivatives as tubulin polymerization inhibitors - Al-Wahaibi, Lamya H.; Elshamsy, Ali M.; Ali, Taha F. S.; Youssif, Bahaa G. M.; Bräse, Stefan; Abdel-Aziz, Mohamed; El-Koussi, Nawal A. (Frontiers in Chemistry, 2025)
IntroductionTubulin polymerization inhibitors have emerged as interesting anticancer therapies. We present the design, synthesis, and structural elucidation of novel thiazole-based derivatives to identify novel tubulin inhibitors with potent antiproliferative efficacy and strong inhibition of tubulin polymerization.MethodsThe novel compounds consist of two scaffolds. Scaffold A compounds 10a-e and scaffold B compounds 13a-e. the structures of the newly synthesized compounds 10a-e and 13a-e were validated using 1H NMR, 13C NMR, and elemental analysis.Results and DiscussionThe most effective antitubulin derivative was 10a, exhibiting an IC50 value of 2.69 μM. Subsequently, 10o and 13d exhibited IC50 values of 3.62 μM and 3.68 μM, respectively. These compounds exhibited more potency than the reference combretastatin A-4, which displayed an IC50 value of 8.33 μM. These compounds had no cytotoxic effects on normal cells, preserving over 85% cell viability at 50 μM. The antiproliferative experiment demonstrated that compounds 10a, 10o, and 13d displayed significant activity against four cancer cell lines, with average GI50 values of 6, 7, and 8 μM, equivalent to the reference’s doxorubicin and sorafenib. Compounds 10a, 10o, and 13d were demonstrated to activate caspases 3, 9, and Bax, while down-regulating the anti-apoptotic protein Bcl2. Molecular docking studies demonstrated superior binding affinities for 10a (-7.3 kcal/mol) at the colchicine binding site of tubulin, forming key hydrophobic and hydrogen bonding interactions that enhance its activity. ADMET analysis confirmed favorable drug-like properties, establishing these compounds as promising candidates for further development as anticancer agents targeting tubulin polymerization.